2019
DOI: 10.1108/jmd-02-2019-0057
|View full text |Cite
|
Sign up to set email alerts
|

Volunteering drivers and continuation will: the role of engagement

Abstract: Purpose As volunteering research in nonprofit organizations is growing significantly, the purpose of this paper is to examine the effects of volunteering drivers and work engagement on volunteer continuation will. Design/methodology/approach Building on empirical and theoretical perspectives, the authors hypothesized that work engagement mediates the relationship between volunteering drivers and volunteer continuation will. To verify our hypotheses, we examined data collected from 372 active volunteers from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
16
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 88 publications
6
16
0
5
Order By: Relevance
“…Research confirmed that integrity (FLI), assurance (FLA), and pragmatism (FLP) are perceived as ethical and predicted organizational commitment. This investigation previously supported findings that ethical leadership is a significant predictor of organizational commitment (Aboramadan et al, 2019). Thus, FLT's theoretical framework that predicted organizational commitment (Fuller, 2021) should influence work engagement.…”
Section: Literature Reviewsupporting
confidence: 78%
See 2 more Smart Citations
“…Research confirmed that integrity (FLI), assurance (FLA), and pragmatism (FLP) are perceived as ethical and predicted organizational commitment. This investigation previously supported findings that ethical leadership is a significant predictor of organizational commitment (Aboramadan et al, 2019). Thus, FLT's theoretical framework that predicted organizational commitment (Fuller, 2021) should influence work engagement.…”
Section: Literature Reviewsupporting
confidence: 78%
“…Bakker et al (2013) defined work engagement as the level of an employee's motivation and positive connection to their work. As a result, much attention has been given to factors influencing work engagement Aboramadan et al, 2019). Comparatively, engagement has been shown to increase organizational commitment and improve employee mental health (Rana et al, 2014;Schaufeli, 2014;Robertson & Cooper, 2010).…”
Section: Leadership Styles On Work Engagementmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Kowske et al (2009) added that work engagement is the degree to which workers are driven to contribute to corporate success and are prepared to make efforts to achieve tasks that are necessary to the attainment of organisational objectives. Individuals who are highly engaged are mentally and emotionally connected to their work and have higher continuation will (Aboramadan et al, 2019;Aboramadan et al, 2020). In contrast, disengaged employees tend to show higher levels of absenteeism, behave negatively and commit unethical practices (Blanchard and Hodges, 2003).…”
Section: Servant Leadership and Work Engagementmentioning
confidence: 99%
“…H4. Transactional leadership has a positive influence on employees' OCB in NPOs 2.5 The role of work engagement Two decades ago, the notion of work engagement received attention from several scholars and practitioners (Aboramadan et al, 2020;Aboramadan et al, 2019;Wollard and Shuck, 2011). According to Bakker et al (2008), work engagement defines the level of motivation and positive connection of an individual to his work.…”
Section: Leadership and Organizational Citizenship Behaviormentioning
confidence: 99%